Properties of Self-Compacting Mortar made with Sorghum Husk Ash and Calcium Carbide Waste as Binder - Hassan, I. O.; Bolaji, O. W.; Adedapo, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The quest for the development of alternative and more sustainable construction material stemmed out from the current global concern on issues relating to global warming and green house effect. In recent time, research direction has shifted towards the use of agro-industrial waste as complete replacement of ordinary Portland cement. In this study the effects of the blends of sorghum husk ash (SHA) and calcium carbide waste (CCW) on the fresh properties of self compacting mortar was investigated where various tests were carried out which included physical and chemical properties of the constituents materials, Flow cone test for paste, Mini v-funnel flow time and Mortar flow spread test for determination of saturation dosage of HRWR for self compacting mortar made with sorghum husk ash and calcium carbide waste as binder, were carried out. Then developments in the compressive strength of the hardened mortar were determined at 3, 7, 14, 28, 56 and 90 days. The study revealed that SHA sample have high Silicon dioxide (SiO2 (84%) while CCW is majorly Calcium oxide (CaO(66%).The optimum saturation dosage of High Range Water Reducer (HRWR) determined from Flow cone test and Mini-v-funnel was 3.5%. The 70/30 (SHA/CCW) shows the highest mortar flow spread of 290 mm compared to the control (295mm).The agro-industrial binder exhibited good binding properties at a slow hydration rate. Analysis of the compressive strength results show that 70/30 (SHA/CCW) proportion has the highest value of 14.08 N/mm2 at 90 days. Self compacting mortar made with SHA/CCW combinations as binder can be adopted for use in masonry work as it conforms to type N of ASTM C270 mortar